ESTUFAS, TELADOS E SUBSTRATOS NO CRESCIMENTO DE MUDAS DE LAVANDA (Lavandula angustifolia Miller) - SOUZA, Larissa Gabriela Pereira; VIEIRA, Mariane Tavares; MARQUES, Ana Leticia Ribeiro; COSTA, Edilson; DUARTE, Ítala Layane (ANAIS DO ENIC, 2023)
-